Trends in injury-related mortality among residents of Jiangsu Province from 2012 to 2021: an age-period-cohort analysis - Du, Wencong; Wang, Rong; Fan, Xikang; Wu, Xun; Yang, Jie; Zhou, Jinyi; Yu, Hao (Frontiers in Public Health, 2024)
Objective We investigated the temporal trends and examined age-, period-, and cohort-specific effects of injury-related deaths among residents in Jiangsu to provide evidence for future injury prevention. Methods This study included 406,936 injury deaths from the Jiangsu provincial population death registration system. The average annual percent change (AAPC) in age-standardized mortality rates (ASMRs) was analyzed using joinpoint regression. Age-period-cohort models were generated to explore the effects of age, period, and birth cohort effects on mortality risk. Results ASMRs for all injuries (AAPC = −2.3%), road traffic accidents (AAPC = −5.3%), suicide (AAPC = −3.8%), and drowning (AAPC = −3.9%) showed a downward trend during 2012–2021(all p < 0.05), while unintentional falls showed an upward trend (AAPC = 5.1%, p < 0.05). From 2012 to 2021, the age-standardized mortality rates (ASMRs) for four primary types of injuries consistently exhibited higher among males compared to females, with rural regions displaying higher ASMRs than urban areas. Trends in ASMRs for road traffic accidents, drowning, and unintentional falls by sex and urban/rural areas were consistent with overall trends. Significant age, cohort, and period effects were identified in the trends of injury-related deaths for both sexes in Jiangsu. The age effect showed that the highest age effect for injury-related deaths was for the ages of 85 years and above, except for suicide, which was for the ages 80–84 years. Between 2012 and 2021, the period effect on road traffic accidents declined, while that on accidental falls increased. Initially, the period effect on suicide decreased but then rose, peaking in 2012 with a Relative Risk (RR) of 1.11 (95% CI: 1.04–1.19). Similarly, the period effect on drowning initially declined before rising, with the highest effect observed in 2013, at an RR of 1.12 (95% CI: 1.07–1.19). The highest cohort effects for road traffic accidents were observed in the 1957–1961 group, for accidental falls in the 1952–1956 group, and for both drowning and suicide in the 1927–1931 group. Conclusion The mortality rate of unintentional falls has been increasing. Older adults are at high risk for the four leading injuries. The improvements in mortality rates can be attributed to advancements in education, urbanization, and the promulgation and implementation of laws and policies.